Implementasi Media Interaktif Pembelajaran Peta Perjalanan Makanan dalam Sistem Pencernaan Manusia Kelas 5 MI Al-Barokah Ajung Jember - Riska Yulianti; Muhammad Suwignyo Prayoga; Nur Hidayah (Universitas Palangka Raya, 2025)
This study aims to improve the understanding of grade 5 MI Al-Barokah students about the learning media of the human digestive system through the application of visual media innovation. A qualitative approach was used in this study with observation techniques and analysis of the teaching and learning process. The results showed that the utilization of visual media was able to help students understand the interactive media learning of the human digestive system more optimally. Students can visually imagine the course of the digestive process and understand various related concepts more clearly. The findings also show that visual media can foster interest and increase student learning motivation. The implication of this study suggests that teachers consider using visual media as an alternative learning strategy in con veying scientific concepts. This research also contributes to the development of more effective and interactive learning approaches to improve students' This research also contributes to the development of more effective and interactive learning approaches to improve students' understanding of scientific material.